Factors associated with risk of major adverse cardiovascular events in patients with rheumatoid arthritis: a nationwide, population-based, case-control study. (August 2021) - Chen, Yen-Ju; Liu, Shih-Chia; Lai, Kuo-Lung; Tang, Kuo-Tung; Lin, Ching-Heng; Chen, Yi-Ming; Tseng, Chih-Wei; Chang, Yu-Mei; Gotcher, Donald F.; Chiou, Chuang-Chun; Weng, Shao-Jen; Chen, Hsin-Hua
Objectives: To investigate factors associated with major adverse cardiovascular events (MACEs) in patients with rheumatoid arthritis (RA). Methods: We conducted a nationwide, population-based, case-control study using Taiwan's National Health Insurance Research Database for 2003–2013. From 2004 to 2012, we identified 108, 319 newly diagnosed RA patients without previous MACEs, of whom 7, 580 patients (7.0%) developed MACEs during follow-up. From these incident RA patients, we included 5, 994 MACE cases and 1:4 matched 23, 976 non-MACE controls for analysis. The associations of MACEs with comorbidities and use of anti-rheumatic medications within 1 year before the index date were examined using conditional logistic regression analyses. Results: Using multivariable conditional logistic regression analysis, the risk of MACE in RA patients was associated with use of golimumab [odd's ratio (OR), 0.09; 95% confidence interval (CI), 0.01-0.67], abatacept (OR, 0.13; 95% CI, 0.02–0.93), hydroxychloroquine (OR, 0.90; 95% CI, 0.82-0.99), methotrexate (OR, 0.72; 95% CI, 0.64–0.81), cyclosporin (OR, 1.43; 95% CI, 1.07–1.91), nonsteroidal anti-inflammation drugs (NSAIDs) (OR, 1.36; 95% CI, 1.27–1.46), antiplatelet agent (OR, 2.47; 95% CI, 2.31-2.63), hypertension (without anti-hypertensive agents: OR, 1.04; 95% CI, 0.96-1.12; with anti-hypertensive agents: OR, 1.47; 95% CI, 1.36-1.59), diabetes (OR, 1.27; 95% CI, 1.18-1.37), hyperlipidemia without lipid-lowering agents (OR, 1.09; 95% CI, 1.01-1.17), ischemic heart disease (OR, 1.20; 95% CI, 1.10-1.31), and chronic obstructive pulmonary disease (COPD) (OR, 1.12; 95% CI, 1.03-1.23) in the parsimonious model. The risk of MACE in RA patients also increased markedly in participants younger than 65 years with some comorbidities. Conclusions: This population-based case-control study revealed that the use of golimumab, abatacept, hydroxychloroquine, and methotrexate were associated with a decreased risk of MACE development in newly diagnosed RA patients, while the use of cyclosporin, NSAIDs, and antiplatelet agents, and comorbidities, including hypertension, diabetes, hyperlipidemia without lipid-lowering agent therapy, ischemic heart disease, and COPD, were associated with an increased risk of MACE development in RA patients.